Interactional linguistics study language in social interaction - Couper-Kuhlen, Elizabeth; Selting, Margret (Cambridge University Press, 2018)
"The first textbook dedicated to interactional linguistics, focusing on linguistic analyses of conversational phenomena, this introduction provides an overview of the theory and methodology of interactional linguistics. Reviewing recent findings on linguistic practices used in turn construction and turn taking, repair, action formation, ascription, and sequence and topic organization, the book examines the way that linguistic units of varying size - sentences, clauses, phrases, clause combinations, and particles - are mobilized for the implementation of specific actions in talk-in-interaction. A final chapter discusses the implications of an interactional perspective for our understanding of language as well as its variation, diversity, and universality. Supplementary online chapters explore additional topics such as the linguistic organization of preference, stance, footing, and storytelling, as well as the use of prosody and phonetics, and further practices with language. Featuring summary boxes and transcripts from recordings of everyday conversation, this is an essential resource for advanced undergraduate and postgraduate courses on language in social interaction"--Provided by publisher.